Pengaruh perubahan iklim terhadap pola kehidupan sosial masyarakat pesisir - Syahrani, Andini (Maliki Interdisciplinary Journal, 2025)
Climate change is one of the global environmental issues that has a direct impact on the lives of coastal communities. Sea level rise, coastal abrasion, seasonal changes and extreme weather intensity have disrupted the economic, social and cultural activities of people who depend on marine resources. Climate change causes a decrease in fishermen’s income, population migration to cities, changes in gender roles in households, and shifts in social and cultural values. Coastal communities carry out various forms of adaptation, such as job diversification, the formation of joint work groups, and strengthening the value of mutual cooperation. However, these adaptations are still limited by unequal access to information, education, and policies. This paper uses the literature study method where the author collects data from research results and also sources from journals, articles and internet sites.